Development of a Strategic Management Model for Effective Procurement Internal Control of Hubei Engineering University, China - Ai, Mingxing; Jinjo, Saichol; Balsiri, Nithipattara (วารสารการวิจัยการบริหารการพัฒนา, 2025)
The objectives of this research were:1) To investigate the needs and expectations of faculty, staff, and administrative staff towards effective procurement internal control of Hubei Engineering University, China. 2)To construct strategic management model based on PDCA Cycle for effective procurement internal control of Hubei Engineering University, China, and 3) To evaluate the effectiveness of strategic management model based on PDCA Cycle for effective procurement internal control of Hubei Engineering University, China. The samples were 284 faculty staffs and 179 administrative staffs of Hubei Engineering University using the Yamane (1967)’s formula. The research instrument used in this research were questionnaire and interview methods, and the questionnaire contained 55 questions, and interview contained 20 questions. The research methodology included population and samples, research instruments, data collection, data analysis, each had 3 phase: Investigate the needs; The focus group meeting; and model evaluation. A five-point scale was used to evaluate the needs and expectations of effective procurement internal control of Hubei Engineering University. Subsequently, this study used questionnaire survey and interview methods to survey 284 teachers and 179 administrative staff of Hubei Engineering University as samples. The questionnaire was verified by 5 experts, using the PDCA management model, and setting four dimensions of planning, doing, checking, and acting. The data were analyzed and by frequency, percentage, mean, and standard deviation etc. The results of this research showed that: 1) The needs and expectations of the faculty staff and administrative staff of Hubei Engineering University regarding procurement internal control were collected. The expectations were at a relatively high level. 2) A strategic management model for effective procurement internal control of Hubei Engineering University was constructed. The strategic management model was based on the PDCA cycle and can be continuously improved and perfected through internal control measures. 3)The strategic management model was evaluated by 5 experts through SWOT analysis, COSO framework and PESTLE analysis. The scores were 3, 2, 3, 3; 3, 3, 2, 3; and 3, 3, 2, 3 respectively. The evaluation values indicate a relatively high level. Practical application shows that this management model has played a significant role in improving the procurement efficiency of Hubei Engineering University, strengthening procurement internal control, and preventing and controlling procurement risks.